Infiltrative Intramuscular Lipoma in the Antebrachium of a Dog - Tirillini, Francesca; Clarke, Stephen; Ferreira, Amy; Baines, Stephen J. (VCOT Open, 2023)
This case report describes a dog with an infiltrative intramuscular lipoma in the antebrachium, presenting with chronic left forelimb lameness and altered posture of the digits. Computed tomography showed a fat-attenuating mass displacing the flexor tendons. The mass was surgically excised along with the affected muscle belly and tendon; histopathological examination revealed infiltration of adipose tissue cells within the muscle belly and tendon sheath of the deep digital flexor muscle. After removal of the lipoma, lameness resolved, full ambulatory function returned, without recurrence at 1 year follow-up.
Keywords: infiltrative lipomas; intramuscular lipomas; dogs; lameness